WAYS TO DEVELOP A GREEN ECONOMY IN A DIGITAL ECONOMY - Khujamberdiyev Tulkin; Yusupova Nasiba Abdujabbarovna (European Science Publishing, 2025)
Article on the importance of the development of a green economy in the digital economy, digital technologies and opportunities for their use, the broad opportunities created by the government for the development of a green economy in Uzbekistan, research theories of scientists and economists supported by their scientific and theoretical foundations for the development of a green economy and increasing employment in the digital economy. "
Keywords: Green economy, digital economy, green energy, energy analysis, environmental crisis, environment.